The Epigenome of Schistosoma mansoni Provides Insight about How Cercariae Poise Transcription until Infection. - David Roquis; Julie M J Lepesant; Marion A L Picard; Michael Freitag; Hugues Parrinello; Marco Groth; Rémi Emans; Céline Cosseau; Christoph Grunau (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Chromatin structure can control gene expression and can define specific transcription states. For example, bivalent methylation of histone H3K4 and H3K27 is linked to poised transcription in vertebrate embryonic stem cells (ESC). It allows them to rapidly engage specific developmental pathways. We reasoned that non-vertebrate metazoans that encounter a similar developmental constraint (i.e. to quickly start development into a new phenotype) might use a similar system. Schistosomes are parasitic platyhelminthes that are characterized by passage through two hosts: a mollusk as intermediate host and humans or rodents as definitive host. During its development, the parasite undergoes drastic changes, most notable immediately after infection of the definitive host, i.e. during the transition from the free-swimming cercariae into adult worms. METHODOLOGY/PRINCIPAL FINDINGS:We used Chromatin Immunoprecipitation followed by massive parallel sequencing (ChIP-Seq) to analyze genome-wide chromatin structure of S. mansoni on the level of histone modifications (H3K4me3, H3K27me3, H3K9me3, and H3K9ac) in cercariae, schistosomula and adults (available at http://genome.univ-perp.fr). We saw striking differences in chromatin structure between the developmental stages, but most importantly we found that cercariae possess a specific combination of marks at the transcription start sites (TSS) that has similarities to a structure found in ESC. We demonstrate that in cercariae no transcription occurs, and we provide evidences that cercariae do not possess large numbers of canonical stem cells. CONCLUSIONS/SIGNIFICANCE:We describe here a broad view on the epigenome of a metazoan parasite. Most notably, we find bivalent histone H3 methylation in cercariae. Methylation of H3K27 is removed during transformation into schistosomula (and stays absent in adults) and transcription is activated. In addition, shifts of H3K9 methylation and acetylation occur towards upstream and downstream of the transcriptional start site (TSS). We conclude that specific H3 modifications are a phylogenetically older and probably more general mechanism, i.e. not restricted to stem cells, to poise transcription. Since adult couples must form to cause the disease symptoms, changes in histone modifications appear to be crucial for pathogenesis and represent therefore a therapeutic target.